A MODEL FOR ASSESSING STUDENTS’USE OF APOLOGY STRATEGIES - Tatang Sopian (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
Working as teacher in a tourism higher "education" that is running diploma program in hospitality services is quite challenging. The diploma programs emphasize development of student professional competency that includes knowledge, skills, and attitude. In term of English language teaching the heavy is put on developing speaking competency, especially to those programs that require direct guest-contacts such as Food and Beverage program that produces among others waiters, or Rooms Division program that produces among others receptionist. Finding effective and efficient ways to evaluate students performance is not an easy task. Taking notes of students’ performance during an oral role-play practice of handling complaint topic can be challenging. So is when the teacher evaluates students’ written works on the same topic. Teacher will have to note many ‘empirical examples’ using easy to follow ways that later when it is used as feedback will be understandable for students so that students learning may improve. Empirical examples notes of students’ performances may vary from word-choice to grammatical mistakes, but this study focus on the employment of Blum-Kulka’s five apology strategies that is used in handling complaint situation. The five apology strategies are 1) Illocutionary Force Indicating Device (IFID), 2) Taking on Responsibility, 3) Explanation or Account, 4) Offer of Repair, and 5. Promise of Forbearance. A model of assessment is made by applying simple coding of the possible combinations use of the five strategies. The apology strategies are coded 1 to 5 while possible combination use the five strategies are coded a to z and more. So, for example a combination is coded “k” represents the use of apology strategies of 1+2+4 or IFID + Taking on Responsibility + Offer of Repair. The assessment model was applied to measure the use of apology strategies in handling complaint situations to students of four well-known tourism higher educations in Indonesia located in Medan, Bandung, Makassar, and Bali. There were eight complaint situations in the DCT or Discourse Completing Test questionnaire in which students have to complete a dialog in written form. These parts of student answer then identified and categorized into one type of combination in the model based on answers given. It is a worth trying alternative of students’ performance evaluation that is helpful for teacher.